Aviation Building, New York World's Fair 1939 (Grinnell Litho Co.)
Located on a large tract of land in the transportation area, the aviation exhibit gives the visitor a realistic picture of a busy metropolitan air port. The exhibit inside the hanger displays the most advanced types of transport planes. The dome-like rear portion holds an invisibly suspended transport plane in full flight against a projected night sky.